An Analysis of Metaphor in Sport News of thejakartapost.com - Tasya Nur Ramadhanti; Senny S Alwasilah; Kunkun K Harnady; Supian S (English Education and Applied Linguistics Journal (EEAL Journal), 2021)
The tittle of this research paper is "An Analysis of Metaphor in Sport News of thejakartapost.com ". This research was conducted with the aim to describe, analyze the types also the meaning purpose of metaphors used in January 1st -31st 2021 sport news of thejakartapost.com. This research is included in research using a qualitative approach. The research data is in the form of word which is assumed to be a metaphor contained in the news. The main research instrument is the kinds of metaphor using Haser theory that transform to the research data classification table. Based on the results of research on the 75 articles in sport news of thejakartapost.com, it was found 20 articles which is using metaphor language. There are 43 metaphors and found 11 Absolute Metaphors (AB), 8 Dead Metaphors (DM), 4 Implied Metaphors (IM), 6 Mix Metaphors (MX), 5 Root Metaphors (RT), and 9 Primary Metaphors (PM). There are types of the usage of the metaphors in every sentence and phrase are almost the same, but the types of metaphor in the sentences and phrases are mostly using a primary and absolute metaphors.